Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/cce.0000000000000309
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes With the Use of Prophylactic Versus Therapeutic Anticoagulation in Coronavirus Disease 2019

Abstract: Objectives: To determine the impact of anticoagulation on inhospital mortality among coronavirus disease 2019-positive patients with the a priori hypothesis that there would be a lower risk of inhospital mortality with use of preemptive therapeutic over prophylactic dose enoxaparin or heparin. Design Setting: Retrospective cohort study from April 1, 2020, to April 25, 2020. The date of final follow-up was June 12, 2020 Two large, acute-care hospitals in Western Connecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 15 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…Among the 8318 articles initially retrieved through our literature search, 21 fulfilled the inclusion criteria and were included in our analysis [ 11 , 12 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The PRISMA 2020 flow diagram for systematic reviews and meta-analyses study selection is presented in Supplementary File, Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 8318 articles initially retrieved through our literature search, 21 fulfilled the inclusion criteria and were included in our analysis [ 11 , 12 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The PRISMA 2020 flow diagram for systematic reviews and meta-analyses study selection is presented in Supplementary File, Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA 2020 flow diagram for systematic reviews and meta-analyses study selection is presented in Supplementary File, Figure S1 . A total of 7 studies reported data for intermediate versus prophylactic dose [ 11 , 27 , 28 , 29 , 30 , 34 , 35 ], while 17 studies reported data for therapeutic versus prophylactic dose of thromboprophylaxis [ 12 , 23 , 24 , 25 , 26 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Three studies contributed data for both intermediate versus prophylactic and therapeutic versus prophylactic dose analyses [ 29 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Paoliss et al reported that receiving therapeutic LMWH therapy was associated with a lower in-hospital mortality compared to the prophylactic LMWH (13). In contrast, in the study of Motta et al, the mortality was 2.3 times higher in patients, who received therapeutic dose LMWH than those, who received prophylactic dose LMWH (14). Musoke et al emphasized the higher mortality and increased bleeding complications in those receiving therapeutic dose anticoagulant therapy (15).…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing number of studies indicating that LMWH is effective in reducing mortality in patients with COVID-19 (6, 7). However, only a few studies compared therapeutic and prophylactic doses of LMWH treatments (13)(14)(15)(16)(17)(18)(19). Whereas some studies showed advantages (7,11) and disadvantages (12-16) of therapeutic LMWH, others found no difference on clinical outcomes/mortality (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“… 10 On the other hand, pre-emptive therapeutic anticoagulation is associated with 2.3 times higher risk of mortality compared with those on prophylactic dose. 11 The current literature on the characteristics of patients that warrant intermediate or therapeutic dose anticoagulation is sparse. Ongoing international trials such as the Randomized, Embedded, Multifactorial Adaptive Platform Trial for Community-Acquired Pneumonia, Antithrombotic Therapy to Ameliorate Complications of COVID-19, and Anti-thrombotics for Adults Hospitalized With COVID-19 aim to address the question whether therapeutic dose anticoagulation is warranted in moderately to critically ill patients.…”
Section: Discussionmentioning
confidence: 99%